Akad Wakalah Bil Ujrah PT. Takaful Keluarga RO Tanwir Nusantara (Gedong Kuning) Yogyakarta Ditinjau Dari Maqasid Syari’ah Imam Syatibi - Fadhila Sukur Indra; Miftahul Huda (University of Darussalam Gontor, 2018)
Insurance as one of the financial institutions engaged in the field of coverage is a modern institution of the findings of the western world that coincided with the spirit of enlightenment (renaissannce). Sharia Asuransi has two contracts tabarru‘ and tijārah contract. Derivatives contained in the tijārah contract is wakālah bil ujrah contract which is one of the transactions in sharia insurance. Islam considers that every transaction or economic activity that occurs must have maṣlaḥah element in it. Imam Syatibi is one of the classical scholars who discuss about the maṣlaḥah with maqāṣid syari’ah. The results of this research will show us the level of syari’ah of the system of the wakālah bil ujrah applied by PT. Takaful Family RO Tanwir Nusantara (Gedongkuning) Yogyakarta with maqāṣid syari’ah Imam Syatibi as the indicator.